Argentina : Third Review Under the Stand-By Arrangement, Request for Waivers and Modification of the Program. (IMF Staff Country Reports; Country Report, 2001)
In 2000, economic activity declined by 0.5 percent, reflecting an 8 percent drop in investment spending. All rated banks, many corporate, several provinces, and the city of Buenos Aires were also downgraded on concerns about growth and the difficult fiscal situation. The performance in regard to structural reforms under the program was uneven. The authorities designed and started the national tax audit plan. Consumer prices are likely to remain broadly unchanged reflecting the still large output gap and the continued high unemployment.